Transient dust in warm debris disks: detection of Fe-rich olivine grains - Olofsson, Johan; Tamanai, Akemi (Astronomy and astrophysics, 2012)
This study focuses on determining the mineralogy of the dust around seven debris disks with evidence for warm dust, based on Spitzer/IRS spectroscopic data, to provide new insights into the origin of the dust grains. We developed and present a new radiative transfer code (Debra) dedicated to spectral energy distribution (SED) modeling of optically thin disks. The Debra code is designed such that it can simultaneously determine dust composition and disk properties. We used this code on the SEDs of seven warm debris disks, in combination with recent laboratory experiments on dust optical properties.
Gesehen am 17.04.2018